2005
DOI: 10.1016/j.cell.2005.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Regulates Programmed Cell Death during the Plant Innate Immune Response

Abstract: The plant innate immune response includes the hypersensitive response (HR), a form of programmed cell death (PCD). PCD must be restricted to infection sites to prevent the HR from playing a pathologic rather than protective role. Here we show that plant BECLIN 1, an ortholog of the yeast and mammalian autophagy gene ATG6/VPS30/beclin 1, functions to restrict HR PCD to infection sites. Initiation of HR PCD is normal in BECLIN 1-deficient plants, but remarkably, healthy uninfected tissue adjacent to HR lesions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
747
4
19

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 783 publications
(797 citation statements)
references
References 48 publications
27
747
4
19
Order By: Relevance
“…20 MDC staining, GFP-LC3 fluorescent localisation and key protein expression levels by Western blot are normally used for autophagy study. 21 LC3 is located on the membrane surfaces of preautophagic vacuoles and autophagic vacuoles. LC3-II reflects autophagy activity to some extent and is a common membrane marker for autophagic vacuoles.…”
Section: Discussionmentioning
confidence: 99%
“…20 MDC staining, GFP-LC3 fluorescent localisation and key protein expression levels by Western blot are normally used for autophagy study. 21 LC3 is located on the membrane surfaces of preautophagic vacuoles and autophagic vacuoles. LC3-II reflects autophagy activity to some extent and is a common membrane marker for autophagic vacuoles.…”
Section: Discussionmentioning
confidence: 99%
“…ROS-induced cell death is implicated in a number of developmental processes and stress responses, including leaf senescence, cell death of root cap cells, and some types of necrosis and HR, depending on the nature of the ROS species [53] and [54]. HR, a form of programmed cell death (PCD) occurs as a plant immune response to survive pathogen attack [55]. Dat et al [54] and Jabs et al [56] identified H 2 O 2 and superoxide anion as initiators of PCD events and necrotic lesion formation, respectively.…”
Section: Asa Treatmentmentioning
confidence: 99%
“…Core sequences have relatively high conservation but exhibit low sequence homology compared with their yeast counterparts. Only plant ATG4 and ATG6 complement yeast knockouts in function (Hanaoka et al, 2002;Liu et al, 2005). Two putative ATG13 genes were found in Arabidopsis, but their similarity is restricted to a relatively small region of the protein and it is currently unclear if they are true ATG13 orthologs (Bassham et al, 2006).…”
Section: Autophagy Mechanism In Plants Core Machinery Of Autophagy Ismentioning
confidence: 99%